Vampires in the lemon grove ebook Stories. - Russell, Karen (2013)
From the author of the novel Swamplandia!— a finalist for the Pulitzer Prize—comes a magical and uniquely daring collection of stories that showcases the author’s gifts at their inimitable best. Within these pages, a community of girls held captive in a Japanese silk factory slowly transmute into human silkworms and plot revolution; a group of boys stumble upon a mutilated scarecrow that bears an uncanny resemblance to a missing classmate that they used to torment; a family’s disastrous quest for land in the American West has grave consequences; and in the marvelous title story, two vampires in a sun-drenched lemon grove try to slake their thirst for blood and come to terms with their immortal relationship. Named a Best Book of the Year by: The Boston Globe O, The Oprah Magazine Huffington Post The A.V. Club A  Washington Post  Notable Book An  NPR  Great Read of 2013